Graphene‐Modified Photoelectrode for Efficient and Cost‐Effective Dye‐Sensitized Solar Cells - Muhammad Umair Shahid (19500590) (2025)
Dye‐sensitized solar cells (DSSCs) have been attracted as a real class of building‐integrated photovoltaic (BIPV) owing to its natural controllable color transparency, working ability in diffuse light, and low‐cost fabrication. The low photoconversion efficiency (PCE) is the main obstacle for BIPV market. The bilayered structure based on mesoporous TiO2 nanoparticles (NPs) along with TiO2 blocking layer was introduced to obtain high PCE by optimizing the dye adsorption, avoid recombination via direct electrolyte contact, and enhance light‐harvesting ability by providing scattering centers. However, the bilayered structure based on mesoporous TiO2 network offers inferior charge transfer, thus higher recombination and, consequently, low PCE. In our previous studies, we have developed graphene/TiO2 blocking layer, graphene/TiO2 transparent layer, and scattering layer and analyzed individually to improve the electron transport and reduce recombination. In the current work, we have demonstrated the integrated optimized photoelectrode‐based DSSCs via the above‐mentioned previously developed photoelectrode components with Pt and graphene/polyaniline (PANI) cost‐effective counter electrode. Optical property analysis and electrochemical impedance spectroscopy (EIS) have shown that graphene‐modified optimum components of photoelectrode have effectively improved the electron transport and light‐harvesting ability. Electron lifetime, diffusion coefficient, and diffusion length have been increased by ~87%, ~20%, and ~11%, respectively, as compared to control DSSC based on commercial paste. Consequently, 5.94% of PCE was achieved, which is 20% higher than the DSSCs fabricated with commercial pastes. Moreover, DSSCs based on optimized photoelectrode with graphene/PANI counter electrode have shown 4.04% PCE, which is ~70% of the PCE that was achieved with Pt. Other Information Published in: International Journal of Energy Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1155/er/6672843